Examination of Pairing Mechanism, Orbital Hybridization, Stabilization and Magnetization Behavior of Tb/Y and Zn/Cu Partially Substituted Y-123 Superconductors - Öztürk, Özgür; Güdücü, G.; Safran, Serap; Yıldırım, Gürcan (Elsevier BV, 2022)
The effect of homovalent Tb/Y and Zn/Cu substitution on electrical, superconducting, structural, and magnetic features of Y-123 ceramic materials is extensively examined by powder X-ray diffraction, electrical resistivity, scanning electron microscopy, energy dispersive X-ray spectrometry, DC magnetization VSM measurements and related calculations. Y1-xTbxBa2Cu3O7-? and YBa2(Cu(1-x)Znx)(3)O(7-? )samples are prepared with four different molar percentages (0.0 <= x <= 0.15) using the sol-gel technique. DC magnetization data and the Bean model are used to evaluate change in critical current densities with an applied magnetic field. Energy-dispersive X-ray spectrometry measurements indicate that materials are exactly produced in the desired stoichiometric ratios. Moreover, all the experimental findings show that the fundamental characteristic properties are observed to decrease with replacement mechanism. The degradation mechanism with partial substitution is thoroughly explained scientifically in the basic contents for the first time. The role of Tb/Y and Zn/Cu partial substitution on the oxygen concentration level in unit cell, ordering degree in the Cu-O ribbons, lattice cell parameters, grain size, and the number of holes in the sigma antibonding in-plane Cu-O bonds are also discussed in detail. Additionally, beginning of weak-interaction problems between adjacent superconductive layers, formation of microscopic structural faults and decoupling of super-conducting grains are noted to be the negative effect of substitution mechanism. Regardless, it is observed that Tb-doped samples possessing more uniform surface morphologies with better surface texture and connection quality between particles show much higher magnetization behavior and superconducting properties. All in all, this study developing a scientific methodology about why fundamental characteristic features change with the partial replacements of Tb/Y and Zn/Cu in crystal systems seems a pioneering investigation to construct novel and feasible application fields for the Y-123 ceramic compounds. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Pairing Mechanism; Flux-Pinning Properties; High-Tc Superconductivity; Partial Substitution; Excess Conductivity; Y-123 Ceramics